Adenomyomatous hyperplasia of distal common bile duct: a case report and review of the literature. Issue 8 (7th August 2018) - Chandler, Paul; Harris, Jonathan; Sherwinter, Danny
Abstract: Adenomyomatous hyperplasia (AH) is commonly found in the gallbladder and is considered a tumor-like inflammatory lesion arising from Rokitansky-Aschoff sinus. It is extremely rare in the extrahepatic bile duct and only 15 cases have been reported to date. We describe a 63-year-old male patient who presented with cholangitis, underwent an extensive diagnostic workup, and ultimately had a Whipple procedure. Final pathology showed a 2.0 × 1.5 × 0.5 cm 3 granular lesion in the distal common bile duct. There was prominent biliary epithelial proliferation with tubular–papillary architecture and minimal nuclear atypia in association with chronic inflammation, stroma reaction and smooth muscle proliferation. AH of the extrahepatic bile duct is a benign process but often requires a major operation to definitively diagnose.